Influence of counter-anions during electrochemical deposition of ZnO on the charge transport dynamics in dye-sensitized solar cells. Issue 3 (4th December 2014) - Richter, Christoph; Beu, Max; Schlettwein, Derck
Abstract : The density of available trap states in porous dye-sensitized ZnO electrodes can be controlled by the proper choice of the counter-anion during electrodeposition of the electrode. It is shown how the electrode kinetics and, hence, the photovoltaic cell properties can be tuned this way. Abstract : Porous ZnO/EosinY films have been electrochemically deposited by oxygen reduction in the presence of a zinc salt from EosinY-containing aqueous solutions, with either chloride or perchlorate as the counter anion. EosinY was removed and the films were sensitised by D149. These electrodes were used for dye-sensitised solar cells (DSCs), and charge transport in the porous network was studied by intensity modulated current/voltage spectroscopy (IMVS/IMPS) and electrochemical impedance spectroscopy (EIS) under illumination. Doping of ZnO during the electrodeposition could be proven by changes in the charge transport in ZnO and could be shown to occur when chloride was used as the counter ion. By using perchlorate as the counter ion, on the other hand, a more reproducible occupation of trap levels was obtained at, however, slightly lower voltages in DSCs whose origin is discussed in detail.